Exposure of hairdressers to ortho- and meta-toluidine in hair dyes. Issue 1 (9th June 2014) - Johansson, Gabriella M; Jönsson, Bo A G; Axmon, Anna; Lindh, Christian H; Lind, Marie-Louise; Gustavsson, Mats; Broberg, Karin; Boman, Anders; Meding, Birgitta; Lidén, Carola; Albin, Maria
Abstract : Background: Carcinogenic aromatic amines derived from hair dyes have recently received new attention. One of these is ortho (o)-toluidine, which is classified as carcinogenic to humans. Objectives: To clarify exposure of hairdressers to potentially carcinogenic aromatic amines, including o-toluidine. Methods: We measured eight potentially carcinogenic aromatic amines in the blood of 295 hairdressers, 32 users of hair dyes and 60 controls. The study was restricted to female non-smokers. Lifestyle data were collected for all participants using self-administered questionnaires. Blood samples were taken for analysis of ortho-, meta (m)- and para (p)-toluidine; 2-, 3- and 4-ethylaniline, 2, 3- and 3, 4-dimethylaniline as haemoglobin adducts. The samples were analysed with gas chromatography–tandem mass spectrometry. Results: Generally, adduct concentrations were in the range of 0–200 pg/g haemoglobin. A comparison of the adduct concentrations found in hairdressers, consumers and controls showed no statistically significant differences. However, for hairdressers, o- and m-toluidine concentrations increased significantly with the weekly number of hair waving (p=0.020) and permanent hair dyeing treatments (p=0.026), respectively. o-Toluidine and m-Toluidine concentrations also tended (p=0.076 and 0.080, respectively) to increase with the frequency of light-colour permanent hair dye treatments. Conclusions: Hairdressers who use light-colour permanent hair dyes, other permanent hair dyes and hair waving treatments seem to be exposed to o- and m-toluidine as indicated by associations with the number of treatments performed. Analyses of hair waving and hair dye products should be performed to identify the possible sources of exposure to o- and m-toluidine.